PEMANFAATAN MAGGOT DALAM PENGLOLAAN LIMBAH ORGANIK RUMAH TANGGA SEBAGAI UPAYA REKAYASA LINGKUNGAN - Kerlima Hutagaol; Agnes Intan Permatasari; Aldy Setiawan; Fandry Oktosa; Kevlin A. Sitorus Pane; Muhammad Hisyam Batubara (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The problem of household organic waste in Indonesia is increasing along with population growth and consumption patterns. Suboptimal waste management can lead to various negative impacts, such as environmental pollution, greenhouse gas emissions, and health problems. One potential solution is the use of Black Soldier Fly (BSF) maggots (Hermetia illucens) as a bioconversion agent in organic waste processing. This study aims to determine the effectiveness of maggots in processing household organic waste and to assess their role as an environmental engineering effort. The research method used was a descriptive quantitative approach through direct observation of the organic waste decomposition process using maggots for 13 days. The organic waste used consisted of various types of household vegetable and fruit waste with a total weight of 10,379 grams. The results showed that the processing process produced 1,245.5 grams of maggot biomass and 1,476 grams of wet compost. Data analysis indicated that approximately 12% of the organic waste was successfully converted into maggot biomass, 14.2% into compost, and the organic waste reduction rate reached 73.8%. These results demonstrate that maggots have a high capacity to reduce organic waste volume quickly and efficiently. In addition to providing environmental benefits by reducing waste generation and greenhouse gas emissions, maggot utilization also produces economically valuable products in the form of high-protein alternative feed and organic fertilizer. Therefore, maggot utilization can be an effective, environmentally friendly, and sustainable environmental engineering solution for managing household organic waste